Applied Aerodynamics Conference 2014 : advanced aero concepts, design and operations : Bristol, United Kingdom, 22-24 July 2014. (Royal Aeronautical Society ; Printed from e-media with permission by Curran Associates, 2015)
The 2014 Royal Aeronautical Society Bi-annual Applied Aerodynamics Research Conference will provide a forum for the presentation and discussion of aspects of the advanced aero concepts, design and operations, covering both the research and the applications. It is intended that the conference will provide an opportunity to raise the profile of the challenges ahead and highlight the technologies required to ensure cost effective solutions in a global market, and in sympathy with the increasingly demanding environmental considerations. The Conference is targeted at aerodynamics researchers and programme managers from academia, industry and research establishments worldwide. The objective being to bring together aerodynamics professionals for a balanced perspective of fundamental science issues, and technological challenges related to current and future developments. -- Provided by publisher.
Keywords: Aerodynamics -- Simulation methods -- Congresses.; Airplanes -- Design and construction -- Simulation methods -- Congresses.; Vehicles -- Design and construction -- Simulation methods -- Congresses.; elektronické knihy; electronic books